2014
DOI: 10.1016/j.jeem.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Utility rebates for ENERGY STAR appliances: Are they effective?

Abstract: We estimate the impact of utility cash rebates on the market share of ENERGY STAR appliances by exploiting the variation in timing and size of rebates across US states. We find that a dollar increase in the (population) weighted utility rebate raises the share of ENERGY STAR qualified clothes washers by 0.4%, but does not affect dishwasher and refrigerator shares. Using information on energy saved by an ENERGY STAR appliance and assuming a redemption rate of 40%, the cost per tonne of carbon saved is about $14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 24 publications
3
35
1
Order By: Relevance
“…We find that the estimated impact of the rebate policies on the sales share of ENERGY STAR appliances ranges from 3.3 percentage points, when using a difference-in-differences approach, to 6.6 percentage points, when using a nonlinear model. The results are higher than the findings in Datta and Gulati (2014) who find that, on average, rebates increase the sales of ENERGY STAR clothes washers by 6%. Our estimates, based on the average sales share of ENERGY STAR appliances, indicate an increase in the sales share of between 9% and 18%.…”
Section: Resultscontrasting
confidence: 74%
See 2 more Smart Citations
“…We find that the estimated impact of the rebate policies on the sales share of ENERGY STAR appliances ranges from 3.3 percentage points, when using a difference-in-differences approach, to 6.6 percentage points, when using a nonlinear model. The results are higher than the findings in Datta and Gulati (2014) who find that, on average, rebates increase the sales of ENERGY STAR clothes washers by 6%. Our estimates, based on the average sales share of ENERGY STAR appliances, indicate an increase in the sales share of between 9% and 18%.…”
Section: Resultscontrasting
confidence: 74%
“…They conclude that the programme is not cost-effective since the cost of reducing CO 2 emissions is over US$500 per tonne. Datta and Gulati (2014) use US state-level data and analyse rebates provided to buyers of ENERGY STAR-qualified clothes washers, refrigerators and dishwashers. They find that utility rebates raise the share of ENERGY STAR qualified clothes washers but do not appear to affect dishwasher and refrigerator shares.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The US government adopted this approach in the State Energy Efficient Appliance Rebate Program (SEEARP), a product of the 2005 Energy Policy Act and the 2009 American Recovery and Reinvestment Act that provided US states and territories with $300 million to fund rebates for energy efficient appliances (MacRae et al 2010). 1 Prior to SEEARP, many US electricity providers offered rebates for energy efficient appliances as a form of demand-side management, typically $25 or $50 for a refrigerator (Datta and Gulati 2010). After SEEARP, most US states began offering rebates ranging from $50 to $700 for an energy efficient refrigerator (USDOE 2010;DSIRE 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Gaspar and Antunes (2011) note that as consumers' purchasing behavior of electrical appliances and energy efficiency are diverse, it is necessary to come up with the ideal eco-label that appeals to every type of consumer. Datta and Gulati (2014) have empirically shown that in the case of high efficiency clothes washers, policies such as subsidies to increase the share of eco-label product are cost effective.…”
Section: Introductionmentioning
confidence: 99%